MORPHOLOGICAL AND MOLECULAR CHARACTERIZATION OF Donax faba (BIVALVIA: DONACIDAE) OBTAINED FROM KUTANG BEACH, LAMONGAN, INDONESIA - Reni Ambarwati; Fida Rachmadiarti; Herlina Fitrihidajati; Tarzan Purnomo; Dwi Anggorowati Rahayu; Ulfi Faizah (BIOTROPIA, 2024)
ARTICLE HIGLIGHTSThis study revealed 19 morphological variations of edible wedge clams, Donax faba (Bivalvia: Donacidae), from Kutang Beach, Lamongan, Indonesia, which has significant role as part of coastal ecosystem.This reseach also highlights the DNA barcoding of Donax faba based on COI gene (Cytochrome C Oxidase Subunit I).The average genetic distance of the research samples was 0.46%, while the value of this parameter between the research samples and the ingroup was found to be 1.51%. ABSTRACTDonax faba is a type of wedge clams with significant ecological and economic roles, as well as variations in color, pattern, and morphometric properties. Recently, a particular population of unidentified D. faba was reported from Kutang Beach, Lamongan, Indonesia. Therefore, this research aimed to assess the morphological variations and molecular characteristics of D. faba obtained from Kutang Beach based on COI gene. A total of 288 samples were collected during the lowest tide for morphological characterization of the color, pattern, and morphometrics of the shells. Additionally, molecular characterization was conducted based on the composition of nucleotide bases and amino acids of COI gene, genetic distance, as well as the relationships. The results showed that D. faba had 19 morphological variations, among which the most dominant type contained a whitish exterior with brown spots and a whitish purple interior. The average genetic distance of the samples was 0.46%, while the value was calculated as 1.51% between the samples and the ingroup. Automatic Barcode Gap Discovery (ABGD) analysis performed using a prior maximal distance of 0.001 showed the separation of these species into distinct categories.